Design and validation of a self-efficacy scale in the evaluation of graduate theses in health sciences - Mamani Benito, Oscar (2022)
Introduction. Graduate theses require adequate evaluation to ensure their methodological quality and publishable potential. Objectives. To design and validate a scale of self-efficacy in the evaluation of graduate theses in health sciences jurors (EAE-Te). Methods. Instrumental and cross-sectional study, with the participation of 221 medical, dental, nursing, nutrition and psychology graduate thesis jurors who work in private and state institutions in the three regions of Peru. The scale was designed based on theoretical indicators found in the scientific literature, with a first version of 16 items. Content-based validity was evaluated with Aiken’s V coefficient, construct validity with Exploratory Factor Analysis and reliability with Cronbach’s Alpha coefficient and their respective confidence intervals. Results. Aiken’s V values were favorable for all items. The exploratory factor analysis evidenced a unidimensional model with 13 items (KMO = 0.868; Bartlett = 2302.1; gl = 66; p < 0.001), where the factor reached explains 60.99% of the total variance of the scale and its factor loadings range between 0.605 and 0.872; finally, reliability was acceptable (α = 0.943; 95%CI = 0.92-0.95). Conclusions. the SEA-Te is a unidimensional measure and demonstrates initial psychometric evidence of content-based validity, internal structure and reliability; therefore, it can be applied to assess the level of jurors’ self-efficacy to evaluate graduate theses.